KAJIAN PENERAPAN ASAS ULTRA PETITA PADA PETITUM EX AEQUO ET BONO - Bambang Sugeng Ariadi Subagyono; Johan Wahyudi; Razky Akbar (Yuridika, 2014)
In judicial practice, that more than likely a lawsuit granted by the court , it often demands the principal ( the primary petition ) is accompanied by replacement demand ( petitum subsidiary ). The contents of the demands it usually reads : " ex aequo et bono " or " please take decisions based on fairness and propriety " . The goal is not to be denied that the primary demand is still possible granting of a lawsuit based on the freedom of judges and justice , in a decision handed down by the judge . Independence of judges in adjudicating the petition accompanied lawsuit subsidiary limited by a principle , namely that : a. Judge shall adjudicate all claims section ( vide Article 178 paragraph ( 2 ) and Article 189 paragraph HIR ( 2 ) Rbg ). b. Judge barred verdict on the case is not prosecuted or granted more than required ( vide Article 178 ( 3 ) HIR and Article 189 ( 3 ) Rbg ). This principle is sometimes called the principle of ultra petita the judge's decision, that in the application raises a particular problem when judges have ruled on the petition relating to the subsidiary, then the research we are doing to provide additional insight for all those who want to understand about the application of the principle in the imposition of ultra petita subsidiary petition or petition of ex aequo et bono.